Corporate Financial Distress Prediction: Comparison Of Accounting And Market Models' Performance (Evidence From Kuwait And Muscat Financial Markets) - الطويل, ليلى; مهنا, بلال (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The purpose of this research is to propose a model for predicting financial distress in companies of two different environments (Kuwait and Muscat financial markets), by using accounting variables, financial market variables, macroeconomic variables and additional variables relevant to the prediction of financial distress probability based on two different populations, and to raise the issue of the study scope difference that would result different predictive variable. To construct the models, the study used a sample of 62 non-financial companies divided into two samples; Kuwait financial market (28 Kuwaiti listed companies divided into 14 healthy companies, 14 not healthy), and Muscat financial market (34 Omanean listed companies divided into 17 healthy companies, 17 not healthy). Using the Binary Logistic Regression Analysis, the results of the study show the importance of accounting variables (especially cash flows and profit) in predicting financial distress and its preference over market variables, and the significance of company size and age variables in improving models, however, the macroeconomic variables did not contribute to the model’s building. The common model produced good results when it was used with real data showing a predictive capacity of 72.6%.